An Evaluation of Butoconazole Nitrate 2% Site ReleaseÃ,Â® Vaginal Cream (Gynazole-1Ã,Â®) Compared to Fluconazole 150 mg Tablets (DiflucanÃ,Â®) in the Time to Relief of Symptoms in Patients With Vulvovaginal Candidiasis - Campbell K. Skokos; Larry S. Seidman (Hindawi Limited, 2005)
Background. It is estimated that as many as 13 million cases of vulvovaginal infection occur in the United States annually, the majority of which are the result of Candida albicans infection. The symptoms of vulvovaginal infections are often painful and distressing to the patient. The objective of this study was to compare the time to symptomatic relief of vulvovaginal candidiasis (VVC) with butoconazole nitrate 2% Site ReleaseÃ,Â® vaginal cream (Gynazole-1Ã,Â®) and oral fluconazole 150 mg tablets (DiflucanÃ,Â®).